x to the 4th power=x^4
2x squared =2x^2
2x cubed= 2x^3
3x squared=3x^2
x^4 + 2x^2 - 2x^3 - 3x^2=
=x^4 - 2x^3 - x^2
=x^2 (x^2 - 2x - 1)
=(x^2)((x + 1)(x - 1) - 2x)
or
=(x^2)((x-1)(x-1) - 2)
2007-04-25 07:00:29
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
2x^2 - 12x = -14 placed -14 on the different section 2x^2 - 12x +14 = 0 divide both section via 2 x^2 -6x +7 = 0 placed 7 on the different section x^2 -6x = -7 you divide the middle time period and sq. it, upload on both section x^2 - 6x + ((6/2)^2) = -7 + ((6/2)^2) Simplify x^2 - 6x + 9 = -7 + 9 Simplify x^2 - 6x + 9 = 2 x^2 - 6x + 9 = (x-3)^2 (x-3)^2 = 2 sq. root both section (x-3) = plus or minus the sq. root of two subtract 3 on both section x = 3 plus the sq. root of two and three minus the sq. root of two
2016-12-04 20:42:40
·
answer #2
·
answered by blacker 4
·
0⤊
0⤋
I assume youre asking me to simplify:
(x^4) + (2x)^2 - (2x)^3 - (3x)^2
= x^4 - 8 * (x^3) - 5 * (x^2)
2007-04-25 06:56:12
·
answer #3
·
answered by Gunmann 1
·
0⤊
1⤋
x^4-2x^3-x^2
=x^2(x^2-2x-1)
2007-04-25 06:48:25
·
answer #4
·
answered by raj 7
·
1⤊
0⤋
x to the fourth power - two x cubed - one x squared
2007-04-25 06:52:20
·
answer #5
·
answered by kytigirl200 3
·
0⤊
1⤋
x^2(x^2-2x-1)
2007-04-25 06:51:15
·
answer #6
·
answered by dwinbaycity 5
·
0⤊
1⤋
x^4+2x^2-2x^3-3x^2
x^4-x^2-2x^3
x^2(x^2-2x-1)
2007-04-25 07:21:47
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
1⤋